Startalk : everything you ever need to know about space travel, sci-fi, the human race, the universe, and beyond - Tyson, Neil deGrasse; Liu, Charles, 1968 April 5-; Simons, Jeffrey Lee; National Geographic Society (U.S.) (Washington, D.C. : Natlional Geographic Society Childrens books, 2018)
"Reimagines science's most challenging topics, from how the brain works to the physics of comic book superheroes, in a relatable, humorous way that will attract curious young readers. Featuring vivid photography, thought-provoking sidebars, enlightening facts, and fun quotes from science and entertainment luminaries like Bill Nye and Josh Groban"--Amazon.
Keywords: Earth sciences -- Popular works; Cosmology -- Popular works; Human beings -- Popular works; Science fiction -- Social aspects; Outer space -- Exploration -- Popular works